PATHway to success: Implementation of a multiprofessional acute trauma health care team decreased length of stay and cost in patients with neurological injury requiring tracheostomy. Issue 1 (January 2020) - Perry, Alvin; Mallah, Mike D.; Cunningham, Kyle W.; Christmas, A. Britton; Marrero, Jennifer J.; Gombar, Meridith A.; Davis, Michael L.; Miles, William S.; Jacobs, David G.; Fischer, Peter E.; Sing, Ronald F.; Thomas, Bradley W.
Abstract : BACKGROUND: The aim of this study was to determine whether the implementation of a dedicated multiprofessional acute trauma health care (mPATH) team would decrease length of stay without adversely impacting outcomes of patients with severe traumatic brain and spinal cord injuries. The mPATH team was comprised of a physical, occupational, speech, and respiratory therapist, nurse navigator, social worker, advanced care provider, and physician who performed rounds on the subset of trauma patients with these injuries from the intensive care unit to discharge. METHODS: Following the formation and implementation of the mPATH team at our Level I trauma center, a retrospective cohort study was performed comparing patients in the year immediately prior to the introduction of the mPATH team (n = 60) to those in the first full year following implementation (n = 70). Demographics were collected for both groups. Inclusion criteria were Glasgow Coma Scale score less than 8 on postinjury Day 2, all paraplegic and quadriplegic patients, and patients older than 55 years with central cord syndrome who underwent tracheostomy. The primary endpoint was length of stay; secondary endpoints were time to tracheostomy, days to evaluation by occupational, physical, and speech therapy, 30-day readmission, and 30-day mortality. RESULTS: The median time to evaluation by occupational, physical, and speech therapy was universally decreased. Injury Severity Score was 27 in both cohorts. Time to tracheostomy and length of stay were both decreased. Thirty-day readmission and mortality rates remained unchanged. A cost savings of US $11, 238 per index hospitalization was observed. CONCLUSION: In the year following the initiation of the mPATH team, we observed earlier time to occupational, physical, and speech therapist evaluation, decreased length of stay, and cost savings in severe traumatic brain and spinal cord injury patients requiring tracheostomy compared with our historical control. These benefits were observed without adversely impacting 30-day readmission or mortality. LEVEL OF EVIDENCE: Therapeutic/care management, Level III.